GRAIN SIZE STATISTICAL PARAMETERS AND PALAEOFLOW VELOCITY MEASUREMENTS OF THE TERTIARY PINDOS FORELAND BASIN TURBIDITES - Vakalas, I.; Ananiadis, G.; Kontopoulos, N.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2018)
Pindos foreland is a tertiary turbiditic basin fill trending parallel to the external Hellenides (Aubouin, 1959). The basin is bounded to the east by the Pindos thrust and to the west by the Ionian thrust. Apart of these two major thrusts, minor thrusts separate the basin into linear narrow sub-basins, trending also parallel to the basin axis. For the grain size statistical analysis 35 sandstone samples were collected from sandstone beds in three sections: Metsovo, Amphilochia and Palaiopyrgos. The thickness of the beds ranges from 8 to 25 cm, and comprise Ta, Tb and Te Bouma sequence subdivisions. The samples were smashed in small pieces and then they were disaggregated using acetic acid solution. Then the samples were washed with deionized water and prepared for sieve analysis. The results of the sieve analysis were plotted in grain size cumulative diagrams in order to estimate the statistical parameters. Sorting, skewness and kyrtosis were calculated and also the samples were plotted in CM, FM and LM diagrams (Passega, 1957; Passega, 1964) The palaeoflow velocity measurements were estimated using Komar’s model (1985). The results of the above analysis provided the following conclusions: a) Sorting values are decreasing at the top of Metsovo and Palaiopyrgos sections indicating an increase of the sediments immaturity, b) The asymmetry values range from positive to very positive with a trend to increase at he top in the sections of Metsovo and Amphilochia, which shows a dominance of the coarser fraction in the selected samples, c) C-M, F-M, L-M affirms that the sediment was transported to the deeper parts of the basin by turbidity currents. Mean flow velocities at the time of deposition range between 1,86 and 26,59 cm/sec. These values are very much in agreement with those proposed for low-density turbidity currents (<25cm/sec) (Nelson and Nilsen, 1984). A similar velocity range is refereed also by Avramidis (1999) who studied the turbidites of the Middle Ionian zone. In Metsovo and Palaiopyrgos mean flow velocity values increase towards the top of the stratigraphy.